Engagement, Well-being, and Team Cohesion in Global Virtual IT Teams - Šlapáková Losová, Veronika (2025)
This dissertation explores the dynamics of engagement, well-being, and team cohesion in global virtual IT teams through actor-network theory. It integrates frameworks such as open innovation, public value theory, social presence theory, embodiment, and spatiality. The research adopts a structuralist approach and a blend of qualitative methods to explore the post-pandemic organization of work by studying the interplay between virtual actors, their benefits, engagement, and well-being. Key findings reveal the diverse actors, motivations, and engagement mechanisms shaping global virtual teams. The study highlights the significance of social presence for engagement and spatial and embodied aspects that affect well-being, team dynamics, and overall productivity. Practical implications include recommendations for orchestrating innovation ecosystems, evaluating virtual collaboration technologies, fostering engagement, protecting well-being, and measuring engagement in virtual meetings. This research enhances the understanding of how global virtual IT teams can use collaborative technologies to improve performance, well-being, and cohesion. It offers insights for both academic and practical applications in virtual team management.